The perpetual failure of the self in its aspiration for the other as a savior Text reading (Pull your face out of my mirror (Journal of the College of Basic Education, 2023)
Poetry is considered creativity when it is able to reduce ideas and suggest resources without permission or recognition.The true poet is the one who is able to diversify his poetic methods, as if he intends to formulate different structural patterns.in multiple poetic forms in the form of a prose poem, a text poem, a flash poem, or a poetry poemOr in combination with the genres of prose, such as the story, drama, epic, play, and others.. “Poetry